Concentration-dependent diffusion kinetics of Ti-Al binary system at elevated temperatures: Experiments and modeling. (July 2019) - Wu, Hao; Zhang, Shihao; Hu, Haibo; Li, Jinkai; Wu, Junyan; Li, Qinggang; Wang, Zhi
Abstract: The aim of the present work is to investigate the dependence of concentration gradient on diffusion kinetics of Ti-Al binary system at high temperatures, which is a long-standing physical problem that cannot easily addressed by tradition diffusion couple experiments due to the ultralow melting point of Al and complicated compositions of various titanium aluminides. We conceived and established a simplified Fick-based diffusion model, making use of successive concentration gradient, in combination with experiments, to reveal the concentration-governed diffusion behavior. Our results showed an excellent agreement with currently available diffusion models. Therefore this approach was expected to be extensively applied to other binary system with large deviations in the melting points. Graphical abstract: Image 1 Highlights: A simplified Fick-based diffusion model combined with the design of diffusion couples was proposed for fast acquisition of diffusion kinetics. The rationalizations of our model and hypothesis were assessed and validated by comparing with available data as reported in the literatures. Concentration-dependent diffusion kinetic in Ti-Al binary system was investigated at a temperature far more than the melting point of Al.